Intercellular mRNA transfer alters the human pluripotent stem cell state - Yosuke Yoneyama; Ran-Ran Zhang; Mari Maezawa; Hideki Masaki; Masaki Kimura; Yuqi Cai; Mike Adam; Sreeja Parameswaran; Naoaki Mizuno; Joydeep Bhadury; So Maezawa; Hiroshi Ochiai; et al. (Proceedings of the National Academy of Sciences, 2025)
Intercellular transmission of messenger RNA (mRNA) is being explored in mammalian species using immortal cell lines. Here, we uncover an intercellular mRNA transfer phenomenon that allows for the adaptation and reprogramming of human primed pluripotent stem cells (hPSCs). This process is induced by the direct cell contact-mediated coculture with mouse embryonic stem cells under the condition impermissible for primed hPSC culture. Mouse-derived mRNA contents are transmitted into adapted hPSCs only in the coculture. Transfer-specific mRNA analysis shows the enrichment for divergent biological pathways involving transcription/translational machinery and stress-coping mechanisms, wherein such transfer is diminished when direct cell contacts are lost. After 5 d of coculture with mouse embryonic stem cells, surface marker analysis and global gene profiling confirmed that mRNA transfer-prone hPSC efficiently gains a naïve-like state. Furthermore, transfer-specific knockdown experiments targeting mouse-specific transcription factor-coding mRNAs in hPSC show that mouse-derived Tfcp2l1 , Tfap2c, and Klf4 are indispensable for human naïve-like conversion. Thus, interspecies mRNA transfer triggers cellular reprogramming in mammalian cells. Our results support that episodic mRNA transfer can occur in cell cooperative and competitive processes, which provides a fresh perspective on understanding the roles of mRNA mobility for intra- and interspecies cellular communications.